2007
DOI: 10.1111/j.1553-2712.2007.tb02017.x
|View full text |Cite
|
Sign up to set email alerts
|

The Opportunity Loss of Boarding Admitted Patients in the Emergency Department

Abstract: Significantly higher operational revenues could be generated by reducing output delays that restrict optimal utilization of existing ED treatment capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 38 publications
0
29
1
Order By: Relevance
“…3 Downstream effects include ED crowding and compromised capability to provide quality and timely care to other patients. 13,21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Downstream effects include ED crowding and compromised capability to provide quality and timely care to other patients. 13,21 …”
Section: Discussionmentioning
confidence: 99%
“…“Boarding time” in the ED was defined as the timebetween when the ED physician noted the decision to admit the patient (bed control had called the admitting team) and the time of the patient’s departure from the ED. While some ED literature suggests that a two hour delay has negative clinical implications 13 , based on critical care clinical experience, boarding time was dichotomized at 4 hours. For each ICU admission from the ED, we computed whether the ED boarding time exceeded four hours.…”
Section: Methodsmentioning
confidence: 99%
“…The ability to safely discharge patients following a single troponin below the LOD may shorten ED length of stay for these patients, ease overall ED crowding, and save costs for hospitals. 20,21 In our dataset, 17% (148/888; 95% CI 14–19%) of patients with a low-risk HEART score and initial troponin below the LOD were discharged from the ED, suggesting that 17% of our ED population that currently undergoes evaluation with serial troponin testing might be safely discharged after a single troponin.…”
Section: Discussionmentioning
confidence: 84%
“…Occupying ED staff in the provision of care to admitted patients for prolonged periods compromises their ability to deliver emergency care 1 7 9–12. Sprivulis et al have shown that hospital and ED overcrowding is associated with a 30% increase in mortality by Day 2 and Day 7 for patients requiring admission via the ED to an inpatient bed 15.…”
Section: The Problem With Overcrowdingmentioning
confidence: 99%